Student Satisfaction or University Reputation? What Is More Important for A Memorable Student Experience - Elsandra, Yessi; Turay, Tiara (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2025)
Abstract The main objective of this paper is to examine the factors that can predict students' memorable experience in a private university in Padang, West Sumatera. More specifically, it aims to examine the direct and indirect relationship between university reputation, student satisfaction and students' memorable experiences. In addition, this study also aims to know what the most important predictor of students’ memorable experience is. The study employed a quantitative survey to collect data as the questionnaires of the study were distributed to 300 students from a private university in Padang. Smart PLS-SEM version 3.2.8 was used as the software tool to analyze the data of the study. The results showed that university reputation had a positive and significant effect on students' memorable experiences and was a strong predictor of students' memorable experiences. University reputation was also found to be an important variable for memorable student experiences. This study gives the contribution to the body of knowledge through the theoretical framework that established the link between memorable student’s experience and its determinants; student’s satisfaction and university reputation. Additionally, this study provides the opportunity to scholars to theoretically connect student’s satisfaction, university reputation, on memorable student’s directly or indirectly through the mediating effect of university reputation. This present study is distinct from others by identifying, filling, and examining gaps, and provides new academic and practical contributions to the body knowledge. The research highlights the important role of university reputation in establishing memorable student's experience, and this indicates that for a private university students in “one” private university in Padang are more concerned about university reputation rather than any other factors that are examined in this study. Therefore, it is highly recommended for private education providers to concentrate more on university reputation by establishing good accreditation and positive image at the top of university management concern and as a priority strategy to generate a high memorable student experience.